Application of NPK Fertilizer and Chicken Manure for the Growth and Production of Sorghum Plants (Sorghum bicolor (L.) Moench) - Sermita Cherri Salu; Ferny M. Tumbel; Sukmarayu P. Gedoan (Sean Institute, 2026)
Sorghum (Sorghum bicolor (L.) Moench) is a cereal crop that has the potential to be developed as an alternative food source because it is adaptive to suboptimal land. The main obstacle in its development is the management of soil fertility, especially the fulfillment of nutrients nitrogen (N), phosphorus (P), and potassium (K). A combination of organic and inorganic fertilizers is necessary to sustainably increase growth and production. This study aims to analyze the influence of chicken manure and NPK fertilizer and their interaction on the growth and production of sorghum. This study used a two-factorial Group Random Design (RAK) with three replicas. The first factor was chicken manure (control, 5 kg, and 10 kg), and the second factor was NPK fertilizer 16:16:16 (control, 1 g, and 2 g). The parameters observed included plant height, number of leaves, stem diameter, panicle length, seed weight per plant, seed weight per plot, and weight of 100 seeds. The data was analyzed using Minitab version 22 through the General Linear Model (GLM) and the Tukey test at the level of 5%. The results of the study showed that the application of chicken manure, NPK fertilizer, and their interactions had a real effect on the growth and production of sorghum. The combination of K1N1 provided the highest response on most parameters, K2N1 occupied the second-highest position with a relatively stable growth response and yield, and K2N2 excelled at a weight of 100 seeds.